2005
DOI: 10.1002/app.21922
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of natural rubber with Ru[CHCH(Ph)]Cl(CO)(PCy3)2 as a catalyst

Abstract: Ru[CHACH(Ph)]Cl(CO)(PCy 3 ) 2 (where PCy 3 is tricyclohexylphosphine) functions as an efficient catalytic system for the hydrogenation of natural rubber. Furthermore, the addition of an acid plays an important role in promoting the hydrogenation process. The quantitative hydrogenation of natural rubber results in a polymer akin to an alternating ethylene-propylene copolymer. Kinetic studies have been carried out via the monitoring of the amount of hydrogen consumed: first-order behavior has been observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…Hydrogenation of NR can be achieved by both catalytic [4][5][6][7][8] and noncatalytic methods. Hydrogenation of NR can be achieved by both catalytic [4][5][6][7][8] and noncatalytic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation of NR can be achieved by both catalytic [4][5][6][7][8] and noncatalytic methods. Hydrogenation of NR can be achieved by both catalytic [4][5][6][7][8] and noncatalytic methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] One of the most important examples, RuHCl(CO)-A C H T U N G T R E N N U N G (PCy 3 ) 2 (2), has been extensively used for the challenging problem of polymer hydrogenation, a key technology in the synthesis of specialty materials, including engineering elastomers and thermoplastics. [4,5] Complex 2, used either directly or generated in situ, is among the most efficient catalysts in current use for the reduction of C=C bonds in nitrile-butadiene polymers [5][6][7][8] and unsaturated polymers derived from ringopening metathesis polymerization (ROMP). [9,10] Its recent applications to molecular transformations span a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Even homogeneous catalytic hydrogenation, at a higher temperature (1508C) and a shorter reaction time than used for diimide hydrogenation, led to a significant decrease in molecular weight of the hydrogenated rubber. 24 Nang et al 20 also reported that MW of hydrogenated cis-1,4-polyisoprene decreased after hydrogenation via diimide generated in situ.…”
Section: Molecular Weight Of Hydrogenated Natural Rubbermentioning
confidence: 95%